Pascaart van de Zee-custen van Ruslant, Laplant, Finmarcken, Spitsbergen en Novazemla - Wit, Frederik de. (Map Coll (Pusey), 1654)
Scale in German, Spanish, English, and French miles. From: Frederik de Wit. Dutch sea atlas. Amsterdam, 1654. [sheet 4]. Also available online.